Coexistence of atypical adenomatous hyperplasia, minimally invasive adenocarcinoma and invasive adenocarcinoma: Gene mutation analysis - Junya Song; Yinghui Xu; Zhiguang Yang; Yunpeng Liu; Peng Zhang; Xu Wang; Chao Sun; Ye Guo; Shi Qiu; Guoguang Shao; Kewei Ma (Thoracic Cancer, 2021)
Abstract Multiple primary lung cancer (MPLC) refers to the simultaneous occurrence of two or more lung primary malignant tumors in one individual. The detection rate of MPLC has increased significantly in recent years, and the distinction between MPLC and lung metastasis has strong clinical significance. Whole exome sequencing (WES) can clearly identify the heterogeneity between MPLC nodules. Here, we report a case of a 50‐year‐old Asian female without a history of smoking. She underwent a lung computed tomography (CT) scan and three ground‐glass nodules (GGNs) were found which were pathologically confirmed as atypical adenomatous hyperplasia (AAH), minimally invasive adenocarcinoma (MIA) and invasive adenocarcinoma (IA), respectively. We performed WES on the three pulmonary nodules and analyzed the sequencing results. We believe that this is the first published report of a case of “three phases” of lung adenocarcinoma analyzed by WES. Under the same genetic background and internal environment, these three nodules showed significant genetic differences and developed into “three phases” of lung adenocarcinoma. Analysis of the WES results supported the lung adenocarcinoma model from AAH to MIA and IA, and explored possible potential driver genes and therapeutic targets. Key points Significant findings of the study We used WES to analyze the gene mutation status of three tumors in one individual. We found that even if under the same genetic background, AAH, MIA and IA showed significant genetic differences and developed into “three phases” of lung adenocarcinoma. What this study adds Analysis of the WES results supported the lung adenocarcinoma model from AAH to MIA and IA, and explored possible potential driver genes and therapeutic targets.